Effectiveness of additive and multiplicative age correction factors in Karan Fries cattle - Gandhi, R S; Singh, Avtar (The Indian Journal of Animal Sciences, 2012)
A total of 793 first lactation records (793) of Karan Fries cows, progeny of 69 sires, spread over a period of 25 years (1971-1995) were analyzed to develop additive and multiplicative age correction factors for 305-day or less milk yield. Both the age correction factors were equally effective on the basis of mean, F-ratio and RÂ² value; while multiplicative age correction factors were more effective in retaining similar CV (%) for all subclasses of age groups as that of uncorrected data and reducing the residual variance as compared to uncorrected or additively corrected data. It seemed that multiplicative age correction factors were more appropriate for this set of data.